Pemodelan Fungsi Transfer Multivariat untuk Meramalkan Produksi Padi di Sumatera Barat - Kuntum Khairatunnisa; Anneke Iswani Achmad (Bandung Conference Series: Statistics, 2023)
Abstract. Forecasting is a way to predict future events using past and present data. One of the models in forecasting is the transfer function model. The Transfer Function Model is a combination of the characteristics of multiple regression analysis with the characteristics of the time series ARIMA (Autoregressive Integrated Moving Average). In the transfer function model there is an output series (yt) which will be affected by the input series (xt) and the other inputs are combined in one group called the noise or noise series (nt). In this study the objects applied to the multivariate transfer function model are rice production (Y) as the output series, harvested area (X1) and rainfall (X2) as the input series. The data used is from January 2010 to December 2020. The purpose of this study is to find out the model and forecast results for rice production in West Sumatra from January 2021 to December 2022 with a multivariate transfer function model. In this study, a multivariate transfer function model was obtained to predict rice production in West Sumatra Yt=-0,83048Yt-1+(6,02681) X1,t-(-0,83048)(6,02681) X2,t-1+0,0079647X2,t-4-(-0,83048)(0,0079647) X2,t-5-(-0,74556)at-1+ et and the highest forecasting results in 2021, namely February of 266,909 tons of dry milled grain (GKG) and the lowest, namely in May, of 266,408 tons of dry milled grain (GKG) while for 2022 the highest production is in January of 266,560 tons of GKG and the lowest was in March with 266.539 tons of GKG. Keywords: Forecasting, ARIMA, Multivariate Transfer Function, Rice Production. Abstrak. Peramalan adalah cara untuk memprediksi kejadian masa depan dengan menggunakan data masa lalu dan sekarang. Salah satu model dalam peramalan adalah model fungsi transfer. Model Fungsi Transfer merupakan gabungan dari karakteristik analisis regrsi berganda dengan karakteristik deret berkala ARIMA (Autoregressive Integrated Moving Average). Pada model fungsi transfer terdapat deret output (yt) yang akan dipengaruhi oleh deret input (xt) dan input-input lainnya digabungkan dalam satu kelompok yang disebut deret gangguan atau noise (nt). Pada penelitian ini objek yang diterapkan pada model fungsi transfer multivariat yaitu produksi padi (Y) sebagai deret output , luas panen (X1) dan curah hujan (X2) sebagai deret inputnya. Dengan data yang digunakan yaitu dari Januari 2010 sampai Desember 2020. Tujuan dari penelitian ini untuk mengetahui model dan hasil ramalan produksi padi di Sumatera Barat dari Januari 2021 sampai dengan Desember 2022 dengan model fungsi transfer multivariat. Dalam penelitian ini diperoleh model fungsi transfer multivariat untuk meramalkan produksi padi di Sumatera Barat adalah Yt=-0,83048Yt-1+(6,02681) X1,t-(-0,83048)(6,02681) X2,t-1+0,0079647X2,t-4-(-0,83048)(0,0079647) X2,t-5-(-0,74556)at-1+ et dan hasil peramalan tertinggi pada tahun 2021 yaitu bulan Februari sebesar 266,909 ton Gabah Kering Giling (GKG) dan terendah yaitu pada bulan Mei yaitu sebesar 266,408 ton Gabah Kering Giling (GKG) sedangkan untuk tahun 2022 produksi tertinggi yaitu pada bulan Januari sebesar 266,560 ton GKG dan terendah yaitu bulan Maret sebesar 266,539 ton GKG. Kata Kunci: Peramalan, ARIMA, Fungsi Transfer Multivariat, Produksi padi.